Urinary concentrations of phthalate biomarkers and weight change among postmenopausal women: a prospective cohort study - Mary V. Díaz Santana; Susan E. Hankinson; Carol Bigelow; Susan R. Sturgeon; R. Thomas Zoeller; Lesley Tinker; Jo Ann E. Manson; Antonia M. Calafat; Jaymie R. Meliker; Katherine W. Reeves (BMC, 2019)
Abstract Background Some phthalates are endocrine disrupting chemicals used as plasticizers in consumer products, and have been associated with obesity in cross-sectional studies, yet prospective evaluations of weight change are lacking. Our objective was to evaluate associations between phthalate biomarker concentrations and weight and weight change among postmenopausal women. Methods We performed cross-sectional (N = 997) and longitudinal analyses (N = 660) among postmenopausal Women's Health Initiative participants. We measured 13 phthalate metabolites and creatinine in spot urine samples provided at baseline. Participants' weight and height measured at in-person clinic visits at baseline, year 3, and year 6 were used to calculate body mass index (BMI). We fit multivariable multinomial logistic regression models to explore cross-sectional associations between each phthalate biomarker and baseline BMI category. We evaluated longitudinal associations between each biomarker and weight change using mixed effects linear regression models. Results In cross-sectional analyses, urinary concentrations of some biomarkers were positively associated with obesity prevalence (e.g. sum of di (2-ethylhexyl) phthalate metabolites [ΣDEHP] 4th vs 1st quartile OR = 3.29, 95% CI 1.80-6.03 [p trend< 0.001] vs normal). In longitudinal analyses, positive trends with weight gain between baseline and year 3 were observed for mono-(2-ethyl-5-oxohexyl) phthalate, monoethyl phthalate (MEP), mono-hydroxybutyl phthalate, and mono-hydroxyisobutyl phthalate (e.g. + 2.32 kg [95% CI 0.93-3.72] for 4th vs 1st quartile of MEP; p trend < 0.001). No statistically significant associations were observed between biomarkers and weight gain over 6 years. Conclusions Certain phthalates may contribute to short-term weight gain among postmenopausal women.